Prevalence of Obesity in Elementary Schools in Mardin, South-Eastern of Turkey: A Preliminary Study - Inanc, Betul Battaloglu; Sahin, Deniz Say; Oguzoncul, Ayse Ferdane; Bindak, Recep; Mungan, Feride (Galenos Publ House, 2012)
Objective: This research determines the frequency of obesity among primary school-aged children and evaluates the relationship between obesity and family and environmental factors. Material and Methods: Three thousand four hundred sixty students, aged 6-15 years in three primary schools in Mardin city center were taken into the study. Information about eating habits and family-environmental factors were obtained by questionnaire. For each student we calculated the body mass index (BMI) and the >= 97 percentile was defined as obese, and between 85-97th percentile as overweight. These values were calculated with the SPSS statistical program. Chi-square and t-tests were used for analysis. p<0.05 was considered statistically significant. Results: 48.2% of the students were female. In the assessment of body mass index (BMI) the overweight rate for children was 15.78%, the obese rate was 10.57%. The prevalence of obesity according to gender was 9.05% for girls and 11.97% for boys (p<0.01). The mean BMI of the girls in the age group 13-15 is higher than in males of the same age. Those in the higher socio-economic group had a higher prevalence of obesity (p<0.01). Paternal obesity affected child obesity (p<0.01). Children who eat irregular meals (p=0.05), watch more than 2 hours per day TV (p=0.03), were breastfed for less than 6 months (p<0.05) and the mothers' obesity (p<0.05) were found to have a significantly higher prevalence of obesity. Conclusion: Obesity is increasing throughout the world as a health problem. Being obese in childhood and having obese parent(s) are two of the risk factors of being obese in adulthood. Persistence of obesity into adulthood is the most serious aspect of the problem. The therapeutic success rate in obesity is unfortunately not high. Therefore, a preventive strategy involving early identification of those at risk by incorporating body mass assessments to routine childhood growth assessment appears to be the most prudent strategy.
Keywords: Childhood obesity; prevalence; body mass index; Mardin; Turkey